A robust and novel methodology for the optimal targeting of leafy vegetable mix soup formulations. (December 2020) - Mondal, Imdadul Hoque; Rangan, Latha; Uppaluri, Ramagopal V.S.
Abstract: This article addresses a mathematical optimization approach to facilitate the systematic transformation of few underutilized leafy vegetables ( Ipomoea aquatica Forssk, Lagenaria siceraria and Basella alba ) of North-East (NE) India into a sensory and nutritionally rich vegetable soup. The methodology involved a combinatorial optimality of moisture, antioxidant activity and vitamin C content of the dried vegetables mixtures through individual or co-drying methods. Thereafter, for a fixed choice of reconstituted soup formulation, sensory and rheological evaluations were targeted through trial and error based variations in the vegetable mix to corn flour ratio. Thereby, the first step enabled the determination of near optimal formulation to that corresponding to individual drying and necessitates upon a dry vegetable mixture consisting of low moisture content (3.21%), high vitamin C (110.38 mg/100 g) and antioxidant activity (80%) characteristics. The second step enabled the identification of 4:6 ratio of vegetable mix and corn flour with 1:20 solids to water ratio to obtain the best sensory characteristic of 8.4 out of 9. The reconstituted soup exhibited shear thinning pseudo-plastic flow behaviour. Thereby, the article affirms upon the relevance of such practical and viable methodology for the development of low cost vegetable soup formulations using under-utilized horticultural produces of NE India. Highlights: Combinatory mathematical, sensory and rheological approach for soup formulation. Individual drying is preferred than co-drying for optimal soup formulation. Optimal formulation possesses high antioxidant activity and vitamin C. With high sensory scores, formulation shows pseudoplastic shear thinning behaviour.